2018
DOI: 10.1080/02670836.2018.1497130
|View full text |Cite
|
Sign up to set email alerts
|

Impression creep behaviour of TiB2 particles reinforced steel matrix composites

Abstract: Impression creep behaviour of the powder metallurgy processed steel matrix composites was investigated under constant stress at different temperatures in the range of 873–973 K. By using the power-law relationship, the estimated activation energy for unreinforced steel was found to be 149 kJ mol−1 and steel reinforced with 2 and 4 vol.-% TiB2 was found to be 298 and 338 kJ mol−1, respectively indicating better creep resistance of the reinforced steel matrix composites. Dislocation creep is the dominant creep m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…They reported a remarkable increase in wear performance of composites and suggested its potential application for high performance tribological components. Sahoo et al [149] reported similar findings for wear performance of hot pressed steel matrix composite. They observed the positive impact of TiB 2 particles on wear resistance of steel matrix and thereby, making them potential for many applications.…”
Section: Influence Of Controllable Variablessupporting
confidence: 52%
See 3 more Smart Citations
“…They reported a remarkable increase in wear performance of composites and suggested its potential application for high performance tribological components. Sahoo et al [149] reported similar findings for wear performance of hot pressed steel matrix composite. They observed the positive impact of TiB 2 particles on wear resistance of steel matrix and thereby, making them potential for many applications.…”
Section: Influence Of Controllable Variablessupporting
confidence: 52%
“…Sahoo et al. [149] reported similar findings for wear performance of hot pressed steel matrix composite. They observed the positive impact of TiB 2 particles on wear resistance of steel matrix and thereby, making them potential for many applications.…”
Section: Overview Of Dry Sliding Wear Performance Of Smcsmentioning
confidence: 52%
See 2 more Smart Citations